HUBUNGAN PEMANFAATAN SUMBER BELAJAR DENGAN HASIL BELAJAR IPA SISWA SMP NEGERI 4 BAREBBO KABUPATEN BONE - Novira Sagita Idmal; Sri Wahyuni (Jurnal Biotek, 2019)
AbstractThis research is a correlational expost facto research that aims to know the relationship between the use of IPAor science learning resources and the science learning outcomes of students at SMP Negeri 4 Barebbo. The data were collected with questionnaire instruments  and documents to 48 people consist of 1 IPA teacher and 47 students. The data then analyzed descriptively with  statistical analysis and inferential statistics. The result of the study show tcount score > ttable score (0,576 > 0,294 and 0,546 > 0,294).It indicate that there is a positive relationship between the use of learning resources with students’ learning outcomes of IPA at SMP Negeri 4 Barebbo, Bone regency.